Matriz de autoevaluación de riesgo de lavado de activos en las empresas comercializadoras de vehículos del Ecuador - Jacome Tipán, Diego Iván (2025)
The International Standard contained in the 40 Recommendations of the Financial Action Task Force has guidelines for countries to implement Anti-Money Laundering, AntiTerrorist Financing and Anti-Weapons of Mass Destruction Proliferation Financing systems that allow them to strengthen their efforts in the fight against these crimes. Obligated Subjects considered the most important actors since they represent the first line of defense, are responsible for issuing reports to Law Enforcement Authorities and perform due diligence processes that are supported by Risk Based Approach methodologies; these processes are carried out to prevent Criminal Organizations from using these institutions to try to give the appearance of legality to the assets obtained in the commission of their illegal activities. The Risk Self-Assessment Matrix constitutes an important input in the risk management system, since it allows knowing the level of exposure to the risk of Money Laundering and its predicate offenses to the Regulated Entities, this matrix is developed through stages or phases (Analysis of the context, identification, measurement, control and monitoring), the same that are applied to the risk factors (Customers, products, channels and jurisdiction), this matrix allows assigning in a logical and effective way resources to mitigate the identified risks.